2013
DOI: 10.1177/1464884913479055
|View full text |Cite
|
Sign up to set email alerts
|

Re-imagining crisis reporting: Professional ideology of journalists and citizen eyewitness images

Abstract: Re-imagining crisis reporting: Professional ideology of journalists and citizen eyewitness images 2 Re-imagining crisis reporting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 35 publications
2
58
1
3
Order By: Relevance
“…Different types of crises such as natural disasters or terrorist attacks have clearly showed that social networks are important means of communication and assistance (Andén-Papadopoulos and Pantti, 2013). In these cases, the images have become a source of priority information, overthrowing media that are stronger on the Internet, thanks to their capacity to broadcast information at high speed.…”
Section: Social Networking and Imagementioning
confidence: 99%
“…Different types of crises such as natural disasters or terrorist attacks have clearly showed that social networks are important means of communication and assistance (Andén-Papadopoulos and Pantti, 2013). In these cases, the images have become a source of priority information, overthrowing media that are stronger on the Internet, thanks to their capacity to broadcast information at high speed.…”
Section: Social Networking and Imagementioning
confidence: 99%
“…This change was also furthered by the terrorist actions in London (2005), Boston (2013), the UK riots (2011), the protests in Myanmar (2007), the elections in Iran (2009), the Arab Spring (2011)(2012) or the slaughter in Syria (2013). These were all tragic events as well (Andén-Papadopoulos, 2013), in which the values in creating the photograph were not professional (Gillmor, 2006). But the really notable thing about these contributions was the authenticity of those images, proceeding from anonymous citizens who found themselves facing a newsworthy event with their mobile devices.…”
Section: Being In the Right Place At The Right Timementioning
confidence: 99%
“…The images provided by these emitters, although they do not reach professionally acceptable standards (Allan, 2013;Andén-Papadopoulos, 2013), serve as a testimony to the atrocities and tyranny experienced on a daily basis (Gillmor, 2011). Their exclusive character normally makes them into outstanding news in the mass media, as happened with the capture and execution of Saddam Hussein, or the atrocities committed in Abu Ghraib prison.…”
Section: Being In the Right Place At The Right Timementioning
confidence: 99%
See 1 more Smart Citation
“…Samansuuntainen havainto on tehty muuallakin: toimittajat eivät pidä kansalaisten journalismia varsinaisena journalismina, ja valtamedia on soveltanut digitaalisessa sisällössä pitkään journalismin vanhoja toimitusrutiineja ja journalismia koskevia arvoja (Heinonen & Domingo 2009, 70). On kuitenkin myös tuoreita havaintoja siitä, että kontrollin sijaan toimittajat arvostavat yleisön tarjoamia sisältöjä ja arvottavat osallistumisen ja journalismin läpinäkyvyyden näin uudella tavalla profession ihanteiksi (Andén-Papadopoulos & Pantti 2013). Ammattilaisten ja amatöörien välisen suhteen jännite ja orastava rajankäynti -"nascent boundary work", Seth Lewisia (2012, 852) lainaten -onkin keskeinen toimittajien itseymmärrystä koskeva nykytutkimuksen haaste ja havainto: miten journalistit suojelevat professiotaan, sen resursseja ja auktoriteettiasemaa amatööreiltä ja/tai avaavat sitä heitä kohtaan (Örnebring 2013, 36).…”
Section: Osallistuminen Ja Modernin Journalismin Ihanteetunclassified